PENERAPAN SISTEM INFORMASI KEUANGAN DAN DATABASE PELANGGAN GUNA MENDUKUNG PENINGKATAN KINERJA UKM - Audita Nuvriasari; Hasim As’ari (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The objectives of this study were to: (1). Identifying the factors that become obstacles in financial governance and customer databases as well as assessing the interest and readiness of the partnersin adopting the technology and information systems. Results of this study then followed up byproviding an understanding through education and counseling to SMEs on the importance offinancial governance and customer databases in business and (2). Provide skills training for SMEsin using financial information systems and customer database management, and (3). Evaluate themanagement performance of SMEs before and after counseling and training. The partner in thisstudy is 23 SMEs in “Paguyban TEGAR”, Gamplong Tourism Village, Yogyakarta. The methods ofthis study are observation and action research. The implementation of the action program includethe provision of assistance equipment such as printers, financial module, financial software forSMEs and customer database software. Other program implementations are: the provision ofcounseling on financial management and customer databases, and training skills in using financialsoftware and customer databases. The evaluation of the actions carried out by comparing theperformance improvement of financial management and customer database before and aftertraining. Keywords: financial management, database customer, information system, education and training,action research